In situ preparation of ionomer as a tool for triple-phase boundary enhancement in 3D graphene supported Pt catalyst - Gangadharan, Pranav K.; Vijayakumar, Vidyanand; Nediyirakkal, Shijil A.; Fernandez, Roshni Tresa; Siddharthan, V. Adhrika; Kurungot, Sreekumar (Advanced Sustainable Systems, 2021)
For improving the performance of platinum electrocatalysts in polymer electrolyte membrane fuel cells (PEMFCs), it is important to enhance the Pt utilization level in the catalyst systems. A high performing electrocatalyst (Pt/3DNG) is developed for PEMFC applications by using nitrogen-doped 3D graphene (3DNG) as the support material and an in situ grafted active ``triple-phase boundary'' to more precisely control the formation of the proton conducting ionomer interface at the active sites. Considering the 3D morphology of the system, during the electrode fabrication for realistic single-cell evaluation, the concept of in situ generation of the proton conducting-ionomer based ``active triple-phase boundary'' is introduced, which could potentially replace the conventional method of using Nafion ionomer for the electrode preparation. The monomers owing to their small-size can access the pores and inner regions of the 3DNG support, which on UV-curing, undergo polymerization and transform into an ionomer with an extended interfacial network into the nanoregimes of 3DNG. Single cell evaluation of the membrane electrode assembly in a high-temperature PEMFC by using phosphoric acid doped polybenzimidazole membrane demonstrates the utility of the present strategy.
Keywords: electrocatalysts; fuel cells; graphene; oxygen reduction reaction